2021
DOI: 10.1038/s41598-021-81711-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the functional impact of PfRh5 genetic diversity on ex vivo erythrocyte invasion inhibition

Abstract: The PfRh5-Basigin ligand–receptor interaction is an essential step in the merozoite invasion process and represents an attractive vaccine target. To reveal genotype–phenotype associations between naturally occurring allelic variants of PfRh5 and invasion inhibition, we performed ex vivo invasion inhibition assays with monoclonal antibodies targeting basigin coupled with PfRh5 next-generation amplicon sequencing. We found dose-dependent inhibition of invasion across all isolates tested, and no statistically sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 19 publications
6
15
0
Order By: Relevance
“…This was observed with certain SNPs, such as D249G and H170R being found in Dalaba, Mako, and Camp Militaire. C203Y was the only SNP found across all sites, which is expected given our previous documentation of its high prevalence in the region 16 and in other regions of Senegal 17 . Overall, the sample size from each clinic does not truly permit quantitative comparisons of genetic diversity between sites; however some of these trends are interesting and would warrant further investigation in prospective targeted studies.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This was observed with certain SNPs, such as D249G and H170R being found in Dalaba, Mako, and Camp Militaire. C203Y was the only SNP found across all sites, which is expected given our previous documentation of its high prevalence in the region 16 and in other regions of Senegal 17 . Overall, the sample size from each clinic does not truly permit quantitative comparisons of genetic diversity between sites; however some of these trends are interesting and would warrant further investigation in prospective targeted studies.…”
Section: Discussionsupporting
confidence: 75%
“…Overall, 158/189 (83.59%) of the isolates contained at least one mutant allele of PfRh5, relative to the 3D7 reference genome (Figure 2A, Supplementary Figure 1). In total, 90 non-synonymous SNPs were identified from these sequences, of which, only 8 were previously reported in other studies 14,[17][18][19] , and an additional 8 were identified in our previously published data 16 . Of the 74 novel SNPs reported here for the first time, 6 were previously described at the same position but we observed different amino acid substitutions (D52G, D127G, D379G, E362A, T384A, and Y147C) (Figure 2A); Supplementary Table 1).…”
Section: Overall Prevalence Of Known and Novel Snps In Kédougoumentioning
confidence: 99%
See 3 more Smart Citations